2021
DOI: 10.1001/jamasurg.2021.4898
|View full text |Cite
|
Sign up to set email alerts
|

Association of Demographic Factors and Medical School Experiences With Students’ Intention to Pursue a Surgical Specialty and Practice in Underserved Areas

Abstract: IMPORTANCEThe surgical workforce shortage is a threat to promoting health equity in medically underserved areas. Although the Health Resources and Services Administration and the American College of Surgeons have called to increase the surgical pipeline for trainees to mitigate this shortage, the demographic factors associated with students' intention to practice in underserved areas is unknown.OBJECTIVE To evaluate the association between students' demographics and medical school experiences with intention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…In addition, among those interested in surgical specialties, racial and ethnic minority medical students are more likely to report an intent to practice in underserved areas. 7 When asked in 2020, most medical students reported that fit with personality, interest, and skill strongly influenced their specialty choice. 8 More than one-half of respondents cited role model influences as a vital factor in this choice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, among those interested in surgical specialties, racial and ethnic minority medical students are more likely to report an intent to practice in underserved areas. 7 When asked in 2020, most medical students reported that fit with personality, interest, and skill strongly influenced their specialty choice. 8 More than one-half of respondents cited role model influences as a vital factor in this choice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, among those interested in surgical specialties, racial and ethnic minority medical students are more likely to report an intent to practice in underserved areas. 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we provide evidence of another potential benefit of ethnoracial and sex diversity in orthopaedic surgery: intention to practice in underserved areas. Previous studies have explored the characteristics of medical students interested in working with underserved populations 3 , 11 , 12 ; this study uses national data to investigate the characteristics of students who intend to pursue orthopaedic surgery with respect to intent to practice in an underserved area. Those who identified as women, ethnoracial URMs, and first-generation college graduates comprised a significantly lower percentage of students pursuing orthopaedic surgery than all other specialties.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study indicate that compared to the awareness of HaH services, there was a greater willingness to accept HaH care among the subjects. Because of the shortage of medical resources in recent years, healthcare professionals cannot provide adequate medical services to every patient, which results in patients' needs not being fully met and leads to poor healthcare experiences (20,21). In addition, the unfamiliarity of the hospital environment can harm patients' mental health, which is not conducive to their recovery (22).…”
Section: Discussionmentioning
confidence: 99%